Stimulasi Pijat Bayi Sehat di Dusun Pengkol Desa Ceweng Jombang - ariani, pipit; widayati; kusbaryati; riandari, ana (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2023)
The period of infant growth and development is a golden period as well as a critical period for the development of a child aged 0-12 months. It is said to be a critical period because at this time babies are very sensitive to the environment and need nutrition and provide good stimulation for their growth and development. One form of stimulation that is commonly done by parents to babies is tactile stimulation in the form of baby massage. Baby massage provides benefits to both mother and baby. Lack of information about infant massage techniques causes mothers to be unable to massage their babies independently. Therefore this problem is related to efforts to improve healthy baby massage skills for parents who have babies aged 0-24 months in Pengkol Hamlet, Ceweng Village. The purpose of this community service is to provide knowledge and socialization for mothers about massage stimulation for healthy babies. This activity was carried out on June 2, 2023 in Pengkol Hamlet during the Posyandu for babies and toddlers with 17 participants attending along with their babies. The data collection instrument was in the form of pretest and posttest questionnaire sheets. The method used is in the form of counseling about stimulating baby growth and development with baby massage along with the right way to massage babies, practice of baby massage and questions and answers. The result of this community service activity is that community service participants in Pengkol Hamlet understand and are able to practice how to do baby massage in accordance with the procedures that have been submitted. The health center is advised to always carry out counseling or socialization regarding stimulation of baby growth and development with healthy baby massage.   Abstrak Masa tumbuh kembang bayi merupakan masa keemasan sekaligus masa kritis perkembangan seorang anak usia 0-12 bulan. Dikatakan masa kritis karena pada masa ini bayi sangat peka terhadap lingkungan dan membutuhkan asupan nutrisi serta memberikan stimulasi yang baik untuk pertumbuhan dan perkembangannya. Salah satu bentuk stimulasi yang umum dilakukan orangtua kepada bayi yaitu stimulasi taktil dalam bentuk pijat bayi. Pijat bayi memberikan manfaat pada ibu dan bayi. Kurangnya informasi tentang tehnik pijat bayi menyebabkan pada ibu tidak bisa memijat bayinya secara mandiri. Oleh karena itu permasalahan ini berkaitan dengan upaya peningkatan keterampilan pijat bayi sehat pada orangtua yang mempunyai bayi usia 0-12 bulan di Dusun Pengkol Kelurahan Ceweng. Tujuan dari pengabdian masyarakat ini adalah untuk memberikan pengetahuan dan sosialisasi bagi ibu ibu tentang stimulasi pijat bayi sehat. Kegiatan ini dilakukan pada tanggal 2 Juni 2023 di Dusun Pengkol pada waktu posyandu bayi dan balita dengan jumlah peserta yang hadir sebanyak 17 orang ibu sekaligus bayinya. Instrumen pengumpulan data berupa Lembar Quesioner pretest dan posttest. Metode yang dilakukan dalam bentuk penyuluhan tentang stimulasi tumbuh kembang bayi dengan pijat bayi beserta cara memijat bayi yang benar, praktek pijat bayi dan tanya jawab. Hasil dari kegiatan pengabdian masyarakat ini adalah peserta pengabdian masyarakat di Dusun pengkol memahami dan mampu mempraktekkan cara melakukan pijat bayi sesuai dengan prosedur yang telah disampaikan. Disarankan kepada pihak puskesmas agar selalu melakukan penyuluhan atau sosialisasi mengenai stimulasi tumbuh kembang bayi dengan pijat bayi sehat.